Measuring the impact of Wuhan’s COVID-19 lockdown on the growth enterprise market in China - Wang, Li; Huang, Zeyu; Wang, Yanan (Frontiers in Physics, 2023)
We examine the impact of Wuhan’s COVID-19 lockdown on the financial markets based on the data of GEM listed companies. We find that investors had a great response to pandemic related news. Compared with the interest rate cut policy, the targeted RRR reduction policy had a more significant positive influence on the financial markets. Furthermore, in the early stages of COVID-19, there was not a significant effect of distance on the companies’ cumulative abnormal returns (CARs). In an improving pandemic environment, the farther the companies were from Wuhan City, the more positive the impact on their CARs would be.